III-Nitride Ultraviolet Emitters Technology and Applications - Kneissl, Michael; Rass, Jens (Springer Series in Materials Science,, 2016)
This book provides a comprehensive overview of the state-of-the-art in group III-nitride based ultraviolet LED and laser technologies, covering different substrate approaches, a review of optical, electronic and structural properties of InAlGaN materials as well as various optoelectronic components. In addition, the book gives an overview of a number of key application areas for UV emitters and detectors, including water purification, phototherapy, sensing, and UV curing. The book is written for researchers and graduate level students in the area of semiconductor materials, optoelectronics and devices as well as developers and engineers in the various application fields of UV emitters and detectors.